World cinema - Hill, John (Oxford University Press, 2000)
Ranging from pre-1930s Europe to contemporary "Bollywood" musicals, this extensive guide to international film covers areas as diverse as New German, Australian, Indian, and South American cinema. A team of international contributors explains the key arguments and debates involved in the study of world cinema and also provides an overview of the avant-garde, the documentary, and recent technological developments. Featuring illustrations throughout, further reading recommendations, and chapter summaries, World Cinema: Critical Approaches serves as an exceptional text for courses in film and media studies